Application of GIS for Detecting Changes of Land Use and Land Cover in Tasik Chini Watershed, Pahang, Malaysia - Islam, Mir Sujaul; B. S., Ismail; Muhammad Barzani, Gasim; Mohd Ekhwan, Toriman; Sahibin, Abd. Rahim; Zularisam, A. W. (Penerbit UMP, 2012)
The Geographical Information Systems (GIS) was used to detect the temporal and spatial land use changes during the periods 1984, 1990, 2000 and 2002 at the Tasik Chini Watershed. The GIS has the capability of associating information with particular features on a map and creating new relationships that can determine the suitability of various sites for development, evaluating the environmental impact and identifying the best location for the new facilities. The boundary of the study area and four land use maps was digitized. There were only three types of land use in 1984; however this dramatically changed into seven categories in 2002. The three initial types of land use were water bodies, forests and oil palm plantations. The forest area decreased by 861.70 ha in 2002 and forests constituted 75.72% of the study area. The forest areas were converted into six categories of land use. These six categories increased by 740.68 ha in 2002 and covered 15.60% of the total area. The water bodies increased by 240.32 ha and covered 8.68% of the study area. The construction of the weir downstream of the Chini River in 1995 has increased the water bodies in the study area. The ecological, biological and hydrological functions of the lake system have been significantly affected during the past 18 years. The unsystematic and rapid urbanization that occurred in the study area not only caused the loss of important forest and wetlands, but also contributed to water and soil pollution problems.